MISSION STUDIES IN NUSANTARA: A Testimony of Local Philosophy Approach on Bali Island - Yogi Prihantoro; Jatmiko Wahyu Nugroho (MAHABBAH: Journal of Religion and Education, 2020)
Archipelagic communities in Indonesia, today are pluralistic societies, and almost all citizens embrace religion because according to the first value of Pancasila, the Indonesian people are people who recognize the existence of God. In the community, there are intersections even the adoption of philosophy and theology simultaneously, which is manifested in daily worship practices. The philosophy that lives in the land of Nusantara (archipelago) is certainly part of eastern philosophy, and both western and eastern philosophies, there are have same philosophical view about humans and God. This research is qualitative, using case studies, in the form of steps (1) determining the symptoms being examined, (2) finding unit of analysis, (3) determining research questions, (4) gathering information or data, (5) linking criteria to interpret the findings obtained, (6) determine criteria for interpreting findings, (7) link findings. The findings of the study, that as part of a diverse Nusantara society, the community of believers needs an approach to carry out a mission in pluralism. Understanding of local philosophy in the context of theology and philosophy meeting issues. Likewise the fellowship of believers on the island of Bali, an island that has long been known for its culture of society, local wisdom and natural beauty. People in Bali, who are not Christians, when they receive an understandable understanding, are ready to receive salvation and live as disciples of God.